Building resilience and adaptation to climate change in Malawi: Quantitative baseline report - Duchoslav, Jan; Kenamu, Edwin; Gilbert, Rachel; Baulch, Bob; Palloni, Giordano; Gilligan, Daniel O. (International Food Policy Research Institute, 2020)
Building Resilience and Adaptation to Climate Change (BRACC) is a five year program whose main objective is to strengthen the resilience of poor and vulnerable households to withstand current and future weather and climate-related shocks and stresses in four districts in Southern Malawi: Balaka, Chikwawa, Mangochi and Phalombe. Resilience is operationalized as the ability of households to smooth consumption in response to shocks and stresses. This baseline report introduces the evaluation context and describes the BRACC program, details the evaluation design, summarizes main findings from the baseline household survey, and tests whether the randomizations successfully balanced baseline observable characteristics across the treatment arms.